ALD modified ultraviolet radiation resistant organic white thermal control coating and preparation method thereof
Through ALD technology, a combination of pigments such as zirconium dioxide and organic binders was modified, a thermal control coating that was resistant to ultraviolet radiation was prepared, which solved the problem of performance degradation of existing thermal control coatings under ultraviolet radiation, and achieved a longer service life and better thermal control performance.
Patent Information
- Application Number
- CN202410684821.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The performance of existing thermal control coatings deteriorates under ultraviolet radiation, resulting in rapid degradation of thermal control effects and shortening their on-orbit service life.
ALD technology is used to modify pigments such as zirconium dioxide, combined with binders such as silicone resin and acrylate, and prepare a thermally controlled coating that is resistant to ultraviolet radiation through spraying and other processes.
It significantly improves the UV radiation resistance of the thermal control coating, extends the service life of the spacecraft external surface coating, and maintains excellent initial thermal control performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal control materials, and in particular relates to an ALD-modified ultraviolet radiation-resistant organic white thermal control coating and a preparation method thereof. Background Art
[0002] Thermal control coating is an important component of the thermal control system of spacecraft. It can effectively control the temperature of the spacecraft by adjusting the surface thermophysical properties of the spacecraft (solar absorptivity αs and infrared emissivity εh) to ensure the normal working environment inside the spacecraft. Ideally, the absolute surface temperature (T) of an object in space is proportional to the ratio of αs to εh, that is, the thermal balance of the object is controlled by adjusting the solar absorptivity αs / εh on the surface of the object. Thermal control coating can be divided into organic white paint and inorganic white paint according to its composition. Compared with inorganic white paint, organic white paint has excellent adhesion to metal substrates, polyimide, carbon fiber composite materials and other substrates, and it plays an irreplaceable role.
[0003] In addition, since the thermal control coating is located on the outer surface of the spacecraft, it will be directly exposed to the harsh space environment, such as high vacuum, charged particles, ultraviolet radiation, atomic oxygen and space debris. In the harsh space environment, it is worth noting that under ultraviolet radiation, the photon energy is high, which will break chemical bonds, causing the performance of materials, especially organic resins, to degrade, causing aging and discoloration of the coating, affecting the thermal control performance of the coating surface, causing the thermal control effect to degrade rapidly, and shortening its on-orbit service life. In recent years, in order to further improve the thermal control performance of the coating, industry researchers have studied high UV reflective filler systems, such as core-shell structure materials, which combine the performance of internal and external materials and make up for each other's shortcomings, greatly improving the overall performance of the material, such as ZnO@SiO 2 , ZnO@Zn 2 SiO 4 , Zn 2 SiO 4 @SiO 2 ; In addition, mesoporous materials have ordered hexagonal porosity, high thermal and mechanical stability, large surface area and excellent resistance to ultraviolet radiation, such as Zn-SBA-15, Zn-MCM-41, etc. On the other hand, titanium dioxide is a common ultraviolet stabilizer that can absorb almost all ultraviolet bands, thereby improving the ultraviolet radiation stability of the resin. Therefore, it is of great significance to improve the vacuum ultraviolet resistance of organic white thermal control coatings. Summary of the invention
[0004] The purpose of the present invention is to provide an organic white thermal control coating resistant to ultraviolet radiation and a preparation method thereof in view of the problems existing in the prior art. The thermal control coating of the present invention is mainly used for the outer surface of spacecraft such as space satellites, and has the characteristics of low solar absorptivity, high emissivity, high stability, and excellent resistance to ultraviolet radiation. On the one hand, pigments such as zirconium dioxide have a wide band gap and a large refractive index in the ultraviolet range, so that they can reflect part of the ultraviolet light; on the other hand, the surface modification material is an ultraviolet absorber, which can absorb almost all bands of ultraviolet light, thereby avoiding ultraviolet degradation of the organic binder to produce color centers, thereby improving the ultraviolet radiation resistance of the organic white thermal control coating.
[0005] The present invention adopts ALD modified zirconium dioxide to prepare pigment for ultraviolet radiation resistant thermal control coating, and adds binders such as silicone resin, acrylate, potassium silicate, lithium silicate, etc., and prepares the ultraviolet radiation resistant thermal control coating through spraying and other processes. The preparation method of the present invention is simple and easy, and is easy to prepare on a large scale. The obtained thermal control coating has the advantages of stable and controllable quality, excellent ultraviolet radiation resistance, and the like.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing an ALD-modified ultraviolet radiation-resistant organic white thermal control coating, comprising the following steps:
[0008] Step 1: Using ALD to deposit narrow-bandgap ultraviolet absorbing materials on the surface of the thermal control pigment to obtain ultraviolet radiation-resistant thermal control pigment;
[0009] Step 2: adding the UV-resistant thermal control pigment obtained in step 1 to the organic resin, adding a solvent, and sand-grinding and dispersing the mixture to make it uniformly mixed, thereby obtaining a UV-resistant thermal control coating;
[0010] Step 3: coating the ultraviolet radiation resistant thermal control coating obtained in step 2 on the pre-treated substrate, and obtaining the coating after curing.
[0011] Further defined, in step 1, the pigment is placed in the ALD reaction chamber and then processed according to the following steps:
[0012] Step 1: depositing narrow bandgap ultraviolet absorbing material in a nitrogen environment, and cleaning the reaction environment after the reaction is completed;
[0013] Step 2, reacting with an oxygen source under the same conditions as step 1, and cleaning the reaction environment after the reaction is completed;
[0014] Step 3: Repeat steps 1 and 2 in sequence; you are done.
[0015] It is further defined that in step 1, the temperature of the narrow bandgap ultraviolet absorption material source is 25°C-90°C, and the deposition temperature is 100°C-300°C; the pressure in the chamber is 0.05torr-1torr, and the pulse time is 15s-60s; and the reaction environment is cleaned with high-purity nitrogen for 10s-60s to flush away reaction by-products and residual reaction sources.
[0016] It is further defined that in step 2, the oxygen source pulse time is 15s-60s, and the reaction environment is cleaned with high-purity nitrogen for 10s-60s to wash away reaction by-products and residual reaction sources.
[0017] It is further defined that in step 1, the cycle period is 30 cycles-200 cycles, and the ALD deposition formed is a partial deposition, which does not completely cover the pigment surface and is an incomplete coating modification.
[0018] It is further defined that the thermal control pigment is a pigment commonly used in the field of thermal control coatings, such as zinc oxide, zirconium dioxide, zinc titanate or zinc silicate.
[0019] It is further defined that the ultraviolet absorber deposited on the pigment surface by ALD modification treatment is a narrow-bandgap ultraviolet absorbing material such as titanium dioxide and zinc oxide.
[0020] It is further defined that the organic resin in step 2 refers to an organic binder commonly used in the field of thermal control coatings, such as silicone resin, epoxy resin and acrylic resin.
[0021] It is further defined that in step three, the substrate is a metal substrate or an organic composite substrate; the metal substrate can be an aluminum alloy, a magnesium alloy, a titanium alloy, etc.; the organic composite substrate can be a carbon fiber reinforced resin-based composite material, polyimide, etc.
[0022] It is further defined that in step three, the substrate pretreatment refers to pretreatment methods such as sandblasting and sandpaper polishing to remove surface impurities and oxide layers.
[0023] It is further defined that in step three, the coating process refers to coating processes such as spraying, roller coating, brushing and scraping.
[0024] It is further defined that in step three, the curing temperature is between 20° C. and 120° C., and the curing time is between 2 h and 24 h, depending on the curing temperature of the resin system.
[0025] It is further defined that in step three, the coating thickness of the prepared ALD modified UV-resistant organic white thermal control coating is 100 μm-200 μm.
[0026] The present invention also provides an ALD-modified ultraviolet radiation-resistant organic white thermal control coating prepared by any of the above methods.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The ALD modified ultraviolet radiation resistant organic white thermal control coating prepared by the present invention has excellent initial thermal control performance, and the radiation absorption ratio is less than 0.1, achieving a leading level in the industry.
[0029] The ALD modified pigment prepared by the present invention has a simple preparation process and can be prepared on a large scale. The prepared ALD modified organic white thermal control coating has greatly improved ultraviolet radiation resistance, which can ensure the reliability of spacecraft operation and meet the spacecraft's requirements for the stability of the paint-type thermal control coating in the space environment.
[0030] After 5000ESH ultraviolet irradiation, the solar absorptivity of the ALD modified ultraviolet radiation resistant organic white thermal control coating prepared by the method of the present invention is only degraded by Δαs=0.05, which is greatly improved compared with the unmodified coating (Δαs=0.10).
[0031] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Optical photos after the cross-cut test of Example 1 and Comparative Example 1;
[0033] Figure 2 The UV-visible-near infrared reflection spectrum of Example 1 before and after ultraviolet irradiation 5000ESH;
[0034] Figure 3 The UV-visible-near infrared reflection spectrum of Comparative Example 1 before and after ultraviolet irradiation 5000ESH;
[0035] Figure 4 Optical photos of Example 1 before and after ultraviolet irradiation 5000ESH;
[0036] Figure 5 These are optical photographs of Comparative Example 1 before and after ultraviolet irradiation of 5000ESH. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0038] Example 1
[0039] This embodiment provides an ALD-modified UV-resistant organic white thermal control coating and a preparation method thereof.
[0040] The ALD modified UV-resistant organic white thermal control coating of this embodiment is composed of UV-resistant pigment and acrylate binder.
[0041] Preparation of ALD modified UV-resistant thermal control pigment: Using ALD technology, titanium dioxide is modified on the surface of zirconium dioxide. The deposition parameters of ALD titanium dioxide are as follows: the titanium source is titanium isopropoxide, the oxygen source is water, and the carrier gas is high-purity nitrogen; the titanium source temperature is 80°C, the deposition temperature is 175°C; the pressure in the chamber is 0.1torr, and the pulse and cleaning time are: the titanium source pulse is 15s; each titanium source pulse is followed by a 30s clean with high-purity nitrogen; the oxygen source pulse is 10s, followed by a 30s clean with high-purity nitrogen to flush out the reaction by-products and residual reaction sources, and the cycle is 50 cycles. Specifically, the pigment zirconium dioxide is placed in the ALD reaction chamber and then processed according to the following steps:
[0042] Step 1: depositing narrow bandgap ultraviolet absorbing material in a nitrogen environment, and cleaning the reaction environment after the reaction is completed;
[0043] Step 2, reacting with an oxygen source under the same conditions as step 1, and cleaning the reaction environment after the reaction is completed;
[0044] Step 3: Repeat steps 1 and 2 50 times in sequence; you are done.
[0045] Preparation of titanium dioxide modified zirconium dioxide-acrylate thermal control coating: weigh 10g acrylic resin and 50g anhydrous ethanol solvent, stir evenly, add 30g titanium dioxide modified zirconium dioxide pigment, then add 150g zirconium beads, disperse and stir at a speed of 1200rpm for 2h, and then filter to obtain titanium dioxide modified zirconium dioxide-acrylate thermal control coating.
[0046] Preparation of titanium dioxide modified zirconium dioxide-acrylate thermal control coating. The titanium dioxide modified zirconium dioxide-acrylate thermal control coating prepared above is applied on a sandblasted magnesium alloy substrate by air spraying, and then cured at 60°C for 10 hours to obtain a titanium dioxide modified zirconium dioxide-acrylate thermal control coating with a coating thickness of 125μm.
[0047] Example 2
[0048] Preparation of ALD modified UV-resistant thermal control pigment: Using ALD technology, titanium dioxide is modified on the surface of zirconium dioxide. The deposition parameters of ALD titanium dioxide are as follows: the titanium source is titanium isopropoxide, the oxygen source is water, and the carrier gas is high-purity nitrogen; the titanium source temperature is 80°C, the deposition temperature is 175°C; the pressure in the chamber is 0.1torr, and the pulse and cleaning time are: the titanium source pulse is 20s; each titanium source pulse is followed by a 30s clean with high-purity nitrogen; the oxygen source pulse is 15s, followed by a 30s clean with high-purity nitrogen to wash away the reaction by-products and residual reactants, and the cycle is 70 cycles. Specifically, the pigment zirconium dioxide is placed in the ALD reaction chamber and then processed according to the following steps:
[0049] Step 1: depositing narrow bandgap ultraviolet absorbing material in a nitrogen environment, and cleaning the reaction environment after the reaction is completed;
[0050] Step 2, reacting with an oxygen source under the same conditions as step 1, and cleaning the reaction environment after the reaction is completed;
[0051] Step 3: Repeat steps 1 and 2 in sequence; you are done.
[0052] Preparation of titanium dioxide modified zirconium dioxide-silicone thermal control coating: weigh 10g of silicone resin and 50g of ethyl acetate, stir evenly, add 30g of titanium dioxide modified zirconium dioxide pigment, then add 150g of zirconium beads, disperse and stir at a speed of 1200rpm for 2h, and then filter to obtain the titanium dioxide modified zirconium dioxide-silicone thermal control coating.
[0053] Preparation of titanium dioxide modified zirconium dioxide-acrylate thermal control coating. The titanium dioxide modified zirconium dioxide-silicone thermal control coating prepared above is applied on a sandblasted aluminum alloy substrate by air spraying, and then cured at 120°C for 2h to obtain a titanium dioxide modified zirconium dioxide silicone thermal control coating with a coating thickness of 130μm.
[0054] Example 3
[0055] Preparation of ALD-modified UV-resistant thermal control pigments: Zinc oxide was modified on the surface of zirconium dioxide using ALD technology. The deposition parameters of ALD-deposited zinc oxide are as follows: the zinc source is diethyl zinc, the oxygen source is water, and the carrier gas is high-purity nitrogen; the deposition temperature is 120°C; the chamber pressure is 0.2 torr, the zinc source pulse time is 60s, the oxygen source pulse time is 60s, and the pulse and cleaning time: the titanium source pulse is 10s; each zinc source pulse is followed by a 30s clean with high-purity nitrogen; the oxygen source pulse is 10s, followed by a 30s clean with high-purity nitrogen to flush out the reaction by-products and residual reaction sources, and the cycle is 30 cycles.
[0056] Preparation of zinc oxide modified zirconium dioxide-acrylate thermal control coating: weigh 10g acrylic resin and 50g anhydrous ethanol solvent, stir evenly, add 30g zinc oxide modified zirconium dioxide pigment, then add 150g zirconium beads, disperse and stir at a speed of 1200rpm for 2h, and then filter to obtain zinc oxide modified zirconium dioxide-acrylate thermal control coating.
[0057] Preparation of zinc oxide modified zirconium dioxide-acrylate thermal control coating. The zinc oxide modified zirconium dioxide-acrylate thermal control coating prepared above is applied by air spraying on a sandpaper-polished carbon fiber reinforced resin-based composite material substrate, and then cured at 60°C for 10 hours to obtain a zinc oxide modified zirconium dioxide-acrylate thermal control coating with a coating thickness of 125μm.
[0058] Comparative Example 1
[0059] Preparation of zirconium dioxide-acrylate thermal control coating: Weigh 10g acrylic resin and 50g anhydrous ethanol solvent, stir evenly, add 30g zirconium dioxide pigment, then add 150g zirconium beads, disperse and stir at a speed of 1200rpm for 2h, and then filter to obtain zirconium dioxide-acrylate thermal control coating. Use air spray to apply it on a sandblasted aluminum alloy substrate, and then cure it at 60℃ for 10h to obtain a zinc oxide-modified zirconium dioxide-acrylate thermal control coating with a coating thickness of 125μm.
[0060] Comparative Example 2
[0061] Preparation of zirconium dioxide-organic silicon thermal control coating: Weigh 10g of organic silicon resin and 50g of ethyl acetate solvent, stir evenly, add 30g of zirconium dioxide pigment, then add 150g of zirconium beads, disperse and stir at a speed of 1200rpm for 2h, and then filter to obtain zirconium dioxide-organic silicon thermal control coating. Use air spray to apply it on the sandpaper-polished carbon fiber reinforced resin-based composite material substrate, and then cure it at 60℃ for 10h to obtain zinc oxide-modified zirconium dioxide-organic silicon thermal control coating with a coating thickness of 130μm.
[0062] The performance of the ALD modified zirconium dioxide UV-resistant organic white thermal control coatings of Example 1, Example 2, and Example 3 and the zirconium dioxide organic white thermal control coatings of Comparative Example 1 and Comparative Example 2 were tested, and the test method is as follows:
[0063] Adhesion test
[0064] According to the test requirements of GJB2704A-2006 General Specification for Thermal Control Coatings of Spacecraft and GB / T9288-2021 Cross-cut Test for Paint and Varnish Film, the thermal control coatings in the embodiments and comparative examples were subjected to cross-cut tests. The results are shown in Tables 1 and Figure 1 shown.
[0065] Table 1 Adhesion test results of different embodiments and comparative examples
[0066] Test methods Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 GJB2704A-2006 Available through Available through Available through Available through Available through GJB2704A-2006 1 1 1 2 2
[0067] Optical performance testing of coatings
[0068] The LAMBDA 950 UV-VIS-NIR spectrometer produced by Perkin Elmer, USA, was used to measure the solar absorption ratio of the coating. The TEMP 2000A emissivity meter developed by AZ Technology, USA, was used to measure the hemispherical emissivity of the sample in the 3-35 μm band at room temperature. The results are shown in Table 2 and Figure 2 .
[0069] Table 2 Optical performance test results of different embodiments and comparative examples
[0070] Test methods Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Solar Absorption 0.089 0.082 0.903 0.075 0.077 Hemispherical emissivity 0.901 0.867 0.913 0.895 0.856
[0071] UV radiation test
[0072] The UV irradiation test is carried out in accordance with the requirements of the national patent (CN1180838A) and GJB 2502.5-2006. This method is suitable for irradiation tests of coating materials in the near-UV band, especially for long-term UV irradiation simulation tests. The solar absorptivity (αs) of the coating material can be tested in situ at any time before, during and after the test, and the test is safe and reliable. The results before and after UV irradiation are shown in Figure 2-Figure 5 and Table 3.
[0073] Table 3 Optical properties test results of Example 1 and Comparative Example 1 before and after UV irradiation
[0074] Before irradiation αs Before irradiation εh After irradiation, αs After irradiation εh Example 1 0.089 0.901 0.130 0.904 Comparative Example 1 0.075 0.895 0.180 0.901
[0075] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. A method for preparing an ALD-modified UV-resistant organic white thermal control coating, characterized in that: The following steps are involved: Step 1: depositing a narrow bandgap ultraviolet absorbing material on the surface of the thermal control pigment by ALD to obtain a thermal control pigment resistant to ultraviolet radiation; Step 2: adding the ultraviolet radiation resistant thermal control pigment obtained in step 1 to the organic resin, adding a solvent, and sand-grinding and dispersing the mixture to make it uniformly mixed, thereby obtaining an ultraviolet radiation resistant thermal control coating; Step 3: coating the ultraviolet radiation resistant thermal control coating obtained in step 2 on the pre-treated substrate, and obtaining the coating after curing; Wherein, the thermal control pigment is a mixture of one or more of zinc oxide, zirconium dioxide, zinc titanate or zinc silicate in any ratio; the narrow bandgap ultraviolet absorption material is titanium dioxide or zinc oxide; In step 1, the pigment is placed in the ALD reaction chamber and then processed as follows: Step 1, in a nitrogen environment, deposit a narrow bandgap ultraviolet absorption material, the temperature of the narrow bandgap ultraviolet absorption material source is 25°C-90°C, and the deposition temperature is 100°C-300°C; the pressure in the chamber is 0.05torr-1 torr, the pulse time is 15 s-60 s, and the reaction environment is cleaned after the reaction is completed, and the cleaning reaction environment is cleaned with high-purity nitrogen for 10 s-60 s; Step 2, reacting with an oxygen source under the same conditions as step 1, the oxygen source pulse time is 10 s-60 s, and cleaning the reaction environment after the reaction is completed, and the cleaning reaction environment is cleaned with high-purity nitrogen for 10 s-60 s; Step 3: Repeat steps 1 and 2 in sequence; then complete; In step 1, the cycle period is 30 cycles-200 cycles, and the ALD deposition formed is a partial deposition; In step 2, the organic resin is silicone resin, epoxy resin or acrylic resin.
2. The method according to claim 1, characterized in that: In step three, the substrate is a metal substrate or an organic composite material substrate; and the substrate is cured at 20°C-120°C for 2 h-24 h.
3. An ALD modified UV-resistant organic white thermal control coating prepared by the method of claim 1 or 2.
Citation Information
Patent Citations
Home position testing method of thermal control coating material
CN1180838A
Preparation method of white molecular adsorption coating with thermal control function
CN112480727A
Ultraviolet ray shielding powder and manufacturing method therefor
JP2016020417A